The Question of the Armenian Genocide in Taner Akçam’s Intrpretation - Gasparyan, Seda (Armenian Folia Anglistika, 2017)
The present paper aims to reveal the standpoint of the Turkish scholar Taner Akçam in the recognition and condemnation of the Armenian Genocide. The linguistic approach to the study of his considerations of the question, as well as his firm belief concerning the responsibility of the present Turkish government for the shameful actions of their predecessors helps to bring out interesting facts and implied meanings.